Peningkatan Efikasi Diri Berwirausaha Melalui Pelatihan Kewirausahaan Pada Remaja Akhir - Zulkhan Effendy; Muh. Bachtiar (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
A pre-test post-test-control-group design was administered to examine the effects of entrepreneurship training on entrepreneurship efficacy. 24 university students from 17 - 24 years in age were randomly selected and then divided into 2 as experiment and control groups. -Using Mann Whitney U and Wilcoxon techniques for data analysis, the results show that the entrepreneurship training has effectively been proven in enhancing the level of efficacy for entrepreneurship for respondents in late adolescence years. The data demonstrated that the differences in level of efficacy are highly significant before and after the training were administered as well as between the 2 groups prospectively.